Effective range of traditional Malaysian FAD as determined by fish-releasing method - Ibrahim, Sakri; Kawamura, Gunzo; Ambak, Mohd Azmi (undefined, 1990)
An experiment to determine the effective range of a traditional Malaysian FAD, the unjam, was conducted in waters off the Terengganu coast, South China Sea. Seventy-two fish of different species, with a float and line attached as a marker, were released at a distance of 30 m from the unjam and subsequently increased by every 30 m until no fish were observed heading towards the unjam. It was found that the effective range of the unjam was 180 m. Landmark orientation was hypothesized that, as the released fish were all unjam-associated species and residents in the area, they had been familiar with the surroundings and had learnt the "home" unjam. © 1990.